Personal Health Records for Patients with Chronic Disease - Wells, S.; Rozenblum, R.; Park, A.; Dunn, M.; Bates, D.W. (Applied Clinical Informatics, 2014)
Background: Personal health records (PHRs) connected to a physician’s electronic health record system hold substantial promise for supporting and engaging patients with chronic disease. Objectives: To explore how U.S. health care organizations are currently utilizing PHRs for chronic disease populations.Methods: A mixed methods study including semi-structured interviews and a questionnaire was conducted. A purposive sample was developed of health care organizations which were recognized as exemplars for PHRs and were high performers in national patient satisfaction surveys (H-CAHPS or CAHPS). Within each organization, participants were health IT leaders or those managing high-risk or chronic disease populations.Results: Interviews were conducted with 30 informants and completed questionnaires were received from 16 organizations (84% response rate). Most PHRs allowed patients to access health records and educational material, message their provider, renew prescriptions and request appointments. Patient generated data was increasingly being sought and combined with messaging, resulted in greater understanding of patient health and functioning outside of the clinic visit. However for chronic disease populations, there was little targeted involvement in PHR design and few tools to help interpret and manage their conditions beyond those offered for all. The PHR was largely uncoupled from high risk population management interventions and no clear framework for future PHR development emerged.Conclusion: This technology is currently underutilized and represents a major opportunity given the potential benefits of patient engagement and shared decision making. A coherent patient-centric PHR design and evaluation strategy is required to realize its potential and maximize this natural hub for multidisciplinary care co-ordination.Citation: Wells S, Rozenblum R, Park A, Dunn M, Bates DW. Personal health records for patients with chronic disease: A major opportunity. Appl Clin Inf 2014; 5: 416–429 http://dx.doi.org/10.4338/ACI-2014-01-RA-0002
Keywords: Personal health records; electronic health records; chronic disease; adoption